Professores de matemática e os saberes mobilizados em sala de aula : um estudo de caso. - Battalini, Lucia Ines (2008)
The main objective of this research was to identify that knowledge mobilize, in classroom, two teachers of Mathematics in Basic Education, for this, was necessary a deepened study about: of the main trends of the Mathematical Education; of the elements that characterize the didactic knowledge of the professor of Mathematics; e still, on the methodological strategies for the education of the Mathematics indicated by the Curricular Lines of direction of Mathematics of the State of the Paraná: Resolution of Problems, Etnomathematic, Mathematical Modeling, Technological Medias and History of the Mathematics. The inquiry was carried through with two teachers of Mathematics, of the State net of Education to the Regional Nucleus of Education of Paranavaí/Paraná, in the period of November of 2006 the July of 2007, in group of 5ª and 6ª grades of basic education. The adopted methodological procedure was the study of case of qualitative, therefore it is about a study in depth of a situation without the intention of change it the context where if it finds, without producing generalizations. The data had been collected by means of a complementary questionnaire, interviews, comments in classroom, materials as: planning, notebook of pupils and didactic book. Of ownership of these materials we look for to identify what we consider as component basic of the didactic knowledge of the professor: the knowledge of the Mathematics, the knowledge of the resume, the knowledge of the pupil and its processes of learning and the knowledge of the instructional processes. The results of this study had indicated that the particular form that each professor adopts to propitiate the learning of its pupils and the form who mobilize definitive methodological strategies are a composition of the elements that its didactic knowledge composes and is supported by the conceptions of the Mathematics, of its education and learning that constitutes the pedagogical idea of each teacher.